2017
DOI: 10.1051/rees/2017039
|View full text |Cite
|
Sign up to set email alerts
|

A review on technology maturity of small scale energy storage technologies

Abstract: Abstract. This paper reviews the current status of energy storage technologies which have the higher potential to be applied in small scale energy systems. Small scale energy systems can be categorized as ones that are able to supply energy in various forms for a building, or a small area, or a limited community, or an enterprise; typically, they are end-user systems. Energy storage technologies are classified based on their form of energy stored. A twostep evaluation is proposed for selecting suitable storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
0
27
0
3
Order By: Relevance
“…As already discussed in the article the optimization of these nanocomposites concerns several aspects including also the SALD conditions (including coating temperature). Increasing the coating temperature leads generally to better metallic oxide layers (more crystallized and compact layer), [47][48][49] however, for thermally sensitive substrates, plasma-enhanced SALD can be employed to significantly lower processing temperature (< 150 °C). 50,51 Therefore SALD coating deposition at low temperature is possible, potentially associated with a slight drawback effect on certain physical properties of the coated layers.…”
Section: Antireflective Properties Of Zno/al2o3 Bilayer Coatings On Agnw Networkmentioning
confidence: 99%
“…As already discussed in the article the optimization of these nanocomposites concerns several aspects including also the SALD conditions (including coating temperature). Increasing the coating temperature leads generally to better metallic oxide layers (more crystallized and compact layer), [47][48][49] however, for thermally sensitive substrates, plasma-enhanced SALD can be employed to significantly lower processing temperature (< 150 °C). 50,51 Therefore SALD coating deposition at low temperature is possible, potentially associated with a slight drawback effect on certain physical properties of the coated layers.…”
Section: Antireflective Properties Of Zno/al2o3 Bilayer Coatings On Agnw Networkmentioning
confidence: 99%
“…The technology maturity curve in Figure 3 consists of the technology readiness level (TRL) and the stage of market development of energy storage technology for small-scale energy systems. Nguyen et al [ 75 ] obtained TRL results by examining different reviews of energy storage technologies and marked the current state of technology development. Furthermore, the stages of market development are evaluated according to research and development, demonstration, growth and maturity.…”
Section: Maturity Of Pcm For Thermal Storagementioning
confidence: 99%
“…The researchers in [7] discuss the ESS architectures utilized in practice, focusing on the development of the control algorithms to optimize the ESS utilization. The study reported in [8] reviews the maturity of storage energy technologies in order to facilitate the load demand for daily consumption. On the other hand, researchers in [9] review the energy storage system for hybrid electrical vehicles (HEV) application.…”
Section: Introductionmentioning
confidence: 99%